„meggyőződéssel vallott zsidó voltunk mellett a magyar haza hű fiainak érezzük magunkat”: Tradíció és integráció a pécsi izraelita elemi népiskolában - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The aim of the study is to uncover the operation of the Israelite school of Pécs between 1852 and 1948, which played an important role in the social integration of Jews while preserving their traditions. A legal historical approach reveals the evolution of the school’s organisation, the number and denominational affiliation of its students, the professional work of its teachers, the changes in the subjects taught in accordance with the ideology of the eras, as well as the relationship with central and local Jewish and secular authorities. The research is based primarily on archival and contemporary sources.